2014
DOI: 10.1074/jbc.m113.539601
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cell-specific Disruption of Period1 and Period2 Exacerbates Diet-induced Inflammation and Insulin Resistance

Abstract: Background:Circadian clockworks gate macrophage inflammatory responses. Results: Myeloid cell-specific disruption of Period1 and Period2 exacerbates diet-induced adipose and liver inflammation and systemic insulin resistance. Conclusion: Macrophage circadian dysregulation contributes to diet-induced inflammation and metabolic phenotypes in adipose and liver tissues. Significance: Interactions between circadian clocks and pathways mediating adipose tissue inflammation are critical in the development and possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 55 publications
4
95
0
Order By: Relevance
“…40,41 Furthermore, disruption of a circadian gene led to the disruption of hepatic lipid homeostasis in mice, 42 whereas myeloid cell-specific disruption of Per1 and Per2 expression in mice exacerbated both diet-induced inflammation and insulin resistance. 43 A recent study found that mistimed sleep disrupted the daily regulation of global gene expression in humans. 44 As social jetlag disrupts sleep timing, it is thus possible that social jetlag has similar effects on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Furthermore, disruption of a circadian gene led to the disruption of hepatic lipid homeostasis in mice, 42 whereas myeloid cell-specific disruption of Per1 and Per2 expression in mice exacerbated both diet-induced inflammation and insulin resistance. 43 A recent study found that mistimed sleep disrupted the daily regulation of global gene expression in humans. 44 As social jetlag disrupts sleep timing, it is thus possible that social jetlag has similar effects on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…After digestion and centrifugation, the pelleted adipose tissue SVCs were cultured for 7 d, and cultures were then harvested separately at the same time of day (9:00 AM). Adipose tissue SVC samples were independently subjected to fluorescence‐activated cell sorting (FACS) analysis, real‐time PCR analysis of inflammatory cytokines, and bioluminescence analysis of clock gene rhythms by using established methods (9, 20).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically how circadian clock disruption contributes to metabolic disorders is unclear, but the activation of proinflammatory macrophages and inflammatory signaling have been identified as key processes in the physiologic cascade linking clock‐and metabolic‐dysregulated phenotypes. In this regard, global and myeloid cell–specific clock disruption ( Per1 ldc / Per2 ldc ) exacerbates macrophage proinflammatory activation, leading to adipose tissue inflammation and further potentiation of high‐fat diet (HFD)‐induced increases in body weight, systemic insulin resistance, and hyperglycemia (9). Collectively, these observations suggest that macrophage proinflammatory activation and adipose tissue inflammation are critical factors in the mechanism by which circadian clock disruption potentiates diet‐induced metabolic phenotypes.…”
mentioning
confidence: 99%
“…Abnormal regulation of circadian clocks in peripheral tissues is suggested to cause cell dysfunction and chronic diseases (8,30). It has been shown that the clock machinery including nuclear receptors controls inflammatory immune responses (5,17,19,(23)(24)(25)(31)(32)(33). We found that the level and expression of clock proteins (BMAL1 and PER2) and associated nuclear receptors (REV-ERBa) were reduced in PBMCs and sputum cells (mainly inflammatory cells [i.e., macrophages and neutrophils]) and in lungs from smokers and patients with COPD.…”
Section: Original Researchmentioning
confidence: 99%